Electrochemical behavior of carbon steel with bentonite/sand in saline environment. Issue 1 (7th September 2020) - Kitayama, Ayami; Taniguchi, Naoki; Mitsui, Seiichiro
Abstract: Current designs for the geological disposal of high‐level radioactive waste in Japan use carbon steel overpack containers surrounded by a mixed bentonite/sand buffer material, which will be located in a purpose‐built repository deep underground. Though there are many suitable sites for a repository in Japan, the coastal areas are preferable from a logistical point of view. It is, therefore, important to evaluate the long‐term performance of the carbon steel overpack and the mixed bentonite/sand buffer material in the saline groundwaters of coastal areas. In the current study, the passivation behavior and initial corrosion rates of carbon steel with and without mixed bentonite/sand were tested as a function of the pH and salt concentration in representative saline groundwaters. The main findings indicate that the passivation of carbon steel encapsulated in a buffer material will be unlikely in a saline environment, even at high pH (12), and that the corrosion rate of carbon steel is more strongly affected by the presence of the buffer material than by the salt concentration. Abstract : The electrochemical behaviors of carbon steel with compacted bentonite/sand buffer material are investigated in synthetic seawater and diluted synthetic seawater under anaerobic conditions. The results indicate that carbon steel is passivated in pH 12 synthetic seawater and diluted synthetic seawater, but not when a compacted buffer material is present.